Lidocaine-Prilocaine Cream versus Placebo in Conjunction with Lidocaine Injection for Pain Relief during Episiotomy Repair after Normal Vaginal Delivery - Wongvivattanakarn, Lalita; Tangsiriwatthana, Thumwadee (Thai Journal of Obstetrics and Gynaecology, 2025)
Objectives: To study the efficacy of lidocaine-prilocaine cream versus placebo in conjunction with lidocaine injection in relieving pain during episiotomy repair. Materials and Methods: Postpartum women who underwent restrictive episiotomy with second-degree perineal tears from August 2023 to February 2024 were randomly allocated into two groups. In the intervention group, lidocaine-prilocaine cream was applied around the episiotomy wound in conjunction with lidocaine injection, while in the control group, placebo cream was applied instead. The primary outcome was pain intensity during episiotomy repair using a 10-cm visual analogue scale (VAS). Results: Ninety women were randomly assigned into two groups (45 in each group). Pain score during lidocaine injection in the lidocaine-prilocaine cream group was significantly lower compared to the control group (2.45 ± 2.49 vs 3.71 ± 2.73; mean difference (MD) -1.26, 95% confidence interval (CI) -2.07 to -0.46, p = 0.002). Pain scores during perineal muscle repair and perineal skin repair in the lidocaine-prilocaine cream group were significantly lower than the control group (1.95 ± 2.13 vs 3.13 ± 2.34; MD -1.19, 95%CI -2.11 to -0.27, p = 0.012 and 1.87 ± 2.12 vs 3.82 ± 2.86; MD -1.95, 95%CI -2.95 to -0.95, p < 0.001, respectively). Perineal wound complications were not significantly different between groups (p = 0.556). No adverse reactions were found. Conclusion: Lidocaine-prilocaine cream in conjunction with lidocaine injection effectively reduced pain during lidocaine injection, perineal muscle repair, and perineal skin repair without adverse reaction.